REMEASUREMENT REFERENCE POINTS ALONG THE EXCLUSIVE ECONOMIC ZONE (EEZ) BORDER OF INDONESIA AND MALAYSIA - Nurdin, Ikhsan
The Malacca Strait is a waterway located between three countries: Indonesia, Malaysia, and Thailand. In this area, Indonesia and Malaysia still have overlapping maritime claims regarding the boundaries of the Exclusive Economic Zone (EEZ). To date, the issue of the EEZ boundaries between Indonesia and Malaysia has not reached an agreement (BIG, 2020). The lack of agreement on the EEZ boundaries by both countries can lead to various problems, such as difficulties in utilizing the natural resources in the area due to the unclear authority boundaries of Indonesia. Furthermore, with the ambiguity of the EEZ boundaries, conflicts with Malaysia regarding maritime utilization rights may arise at any time. Therefore, the determination of the EEZ boundaries between the two countries must be carried out promptly. According to UNCLOS 1982, establishing maritime boundaries requires accurate baseline points and reference points to ensure the accuracy of the maritime boundaries. Previous research indicated that there have been changes in the baseline and reference points in Weh Island, moving 21 meters seaward between 2017 and 2022 (Putra, 2023). Hence, a re-measurement of reference points in strategic areas, such as the EEZ boundary between Indonesia and Malaysia, is necessary. This study aims to re-measure the reference points of the maritime boundary along the EEZ border between Indonesia and Malaysia in the Malacca Strait segment. It is hoped that this research can determine and ensure the accuracy of the reference points along the EEZ boundary between Indonesia and Malaysia, preventing any disadvantage to either party. The methods employed in this thesis include research planning, literature review, planning for data collection, data processing, data analysis, and conclusions and recommendations. The position measurement of reference points was conducted using static GPS methods. This research produced data indicating changes in the coordinates of the reference points for the Exclusive Economic Zone (EEZ) boundary between Indonesia and Malaysia in the Malacca Strait segment, specifically positions TR 181, TR 182, and TR 183. The positional changes compared to the data in Government Regulation No. 38 of 2002, updated in Government Regulation No. 37 of 2008, show that TR 181 has changed by 0.418 m, TR 182 by 67.747 m, and TR 183 by 156.315 m. It is hoped that this research will contribute to the determination of maritime boundaries, particularly for the strategic EEZ border area between Indonesia and Malaysia in the Malacca Strait segment.